Nas Trilhas do Rei do Cangaço e de suas Representações (1922-1927) - Dutra, Wescley Rodrigues (2011)
The cangaço is configured in the history of Brazilian Northeast, as a relevant movement leaving traces in memory, popular culture and imagery. This movement was not something sudden, but covering a long period, taking down roots in the eighteenth century through the nineteenth and flourishing with greater notoriety in the first half of the twentieth. Countless individuals have emerged as key leaders of gangs. One subject in special marks the social imaginary and the history of the region: the bandit Virgolino Ferrreira da Silva, or only Lampião. For twenty years he swept the interior of seven Northeastern states, becoming a parallel power to the official one. Lampião‟s life was endowed with contradictions, which generated multiple representations on it. Over his image were built speeches which represent him as villain, righteous, ruffian, murderous, rapist, strategist, champion of justice, etc.. Each representation elaborated on the outlaws comes loaded with the stigmas of the interests of various groups and social sectors. An important area of building representations about Lampião was the Northeastern press that, although in its news represent the design of the ruling elite, trying to get negative images about the outlaw, attributed to Lampião the place as the King of Cangaço eventually because of his boldness, courage and constant leakage on the strategies of the steering forces. Having the newspapers as a support document, we turned our attention to two events established in the literature about the cangaço: Lampião‟s stay in Juazeiro do Norte (CE) in 1926 and the defeat of the bandit in Mossoró (RN) in 1927. We analyze the representations constructed in these two different Lampião moments trying to understand how they contributed to the construction of a historical culture of cangaço. To achieve this objective, we use the theoretical concept of representation, from the perspective of the historian Roger Chartier.